Penegakan Hukum Terhadap Penangkapan Ikan Secara Ilegal oleh Kapal Asing - Ritonga, Alvina Hardiyanti; Marpaung, Zaid Alfauza (Universitas Muhammadiyah Ponorogo, 2025)
This study examines law enforcement efforts against illegal fishing practices by foreign vessels in the waters of Belawan, North Sumatra, a strategic area bordering the Malacca Strait and vulnerable to transnational crimes. The primary focus of this research is to analyze the law enforcement model applied in the Belawan maritime area, identify structural and legal obstacles encountered, and evaluate the effectiveness of the approaches used by law enforcement agencies. This study employs a qualitative approach, with data collection techniques including document analysis, field observations, and interviews with relevant stakeholders. Data analysis techniques consist of data reduction, data display, and inductive conclusion drawing. The research findings reveal that the law enforcement model in the Belawan area combines both preventive and repressive measures, involving coordination among institutions such as the Ministry of Marine Affairs and Fisheries (MMAF), the Marine and Fisheries Resources Surveillance (PSDKP), the Indonesian Navy, and community-based surveillance groups (Pokmaswas). A declining trend in the number of apprehended foreign fishing vessels in recent years indicates a degree of success in enforcement. The originality of this study lies in its specific identification of institutional obstacles, such as overlapping authority, limited patrol resources, and the lack of harmonization in maritime legal regulations. Therefore, the study recommends stronger institutional integration, modernization of maritime surveillance technologies, and harmonization of legal frameworks as strategic measures to enhance the effectiveness of law enforcement in Belawan waters and surrounding areas.